Standing in the fire : leading high-heat meetings with calm, clarity, and courage - Dressler, Larry, 1961- (BK business book., 2010)
Standing in the Fire offers a set of self-directed principles and practices that enable facilitators and human resource personnel to keep their emotional balance no matter how overheated things threaten to become in the workplace.